Catechol-rich gelatin microspheres as restorative medical implants intended for inhibiting seroma formation and promoting wound healing - Xinping Wang; Guoqing Wang; Jianfei Wang; Junqiang Xue; Gaoli Liu; Changjiang Fan (Materials Today Bio)
Seroma formation and poor wound healing are common complications of many surgeries that create anatomical dead space (i.e., mastectomy), often causing tissue infection and even necrosis. Although negative pressure drainage and tissue adhesives are investigated to alleviate fluid accumulation post-surgery, however, their therapeutic efficacy remains unsatisfactory in most cases. Herein, the catechol-rich chemically crosslinked gelatin microspheres (ca-CGMSs) have been developed as biodegradable reconstructive implants for preventing seroma formation and concurrently promoting subcutaneous wound healing. Compared with the most representative hydrogel adhesive, i.e. commercial porcine fibrin sealant (PFS), the loosely packed ca-CGMSs with diameters range from 50 to 350 μm, provide numerous cell-adhesive interfaces and interconnected macro-pores for enhanced cell adhesion, proliferation and migration. Subcutaneous embedding trials show the in situ swelling aggregation and wet tissue adhesion of ca-CGMSs as well as their capacity in recruiting autologous cells in rat mastectomy models. The trials in rabbit mastectomy models demonstrate that, compared with PFS gluing, the implanted dried ca-CGMSs not only significantly inhibit seroma formation, but also achieve enhanced wound healing by inducing the formation of vascularized neo-tissue. The ca-CGMSs show a great potential to be the next-generation of restorative materials for both preventing seroma formation and healing subcutaneous wounds.